Positive electrode active material for non-aqueous electrolyte secondary battery and method for producing the same

By using lithium transition metal composite oxide particles of nickel in a nonaqueous electrolyte secondary battery and attaching specific oxides, combined with appropriate aluminum compound particle size distribution and heat treatment, the problem of poor cycling characteristics at high voltage is solved, and the problem of poor cycling characteristics is achieved. Capacity maintenance and performance improvement.

CN111600017BActive Publication Date: 2024-12-20NICHIA CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010101351.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-28
Filing Date
2020-02-19
Publication Date
2024-12-20
Estimated Expiration
2040-02-19

Smart Images

  • Figure CN111600017B_ABST
    Figure CN111600017B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide a positive electrode active material for a non-aqueous electrolyte secondary battery that can reduce the capacity reduction caused by additives and has good cycle characteristics under high voltage. The solution is a positive electrode active material for a non-aqueous electrolyte secondary battery, which has a layered structure and includes lithium transition metal composite oxide particles containing nickel, and oxides containing lithium and aluminum and oxides containing lithium and boron attached to the surface of the above-mentioned lithium transition metal composite oxide particles. The lithium transition metal composite oxide particles contain secondary particles formed by the aggregation of primary particles with aluminum solid dissolved in the surface layer. In the composition of the lithium transition metal composite oxide particles, the difference between the ratio of the molar number of aluminum solid dissolved in the surface layer of the primary particles to the total molar number of metals other than lithium and the ratio of the molar number of aluminum present in the area other than the surface layer of the primary particles to the total molar number of metals other than lithium is greater than 0.22 mol% and less than 0.6 mol%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same. Background Art

[0002] Lithium transition metal composite oxides with a layered structure, such as lithium cobalt oxide and lithium nickel oxide, which are positive electrode active materials for non-aqueous electrolyte secondary batteries, have an operating voltage as high as about 4V and can obtain a large capacity. Therefore, they are widely used as power sources for electronic devices such as mobile phones, notebook computers, and digital cameras, and as vehicle-mounted batteries. With the high functionality of electronic devices and vehicle-mounted batteries, the development of positive electrode active materials for non-aqueous electrolyte secondary batteries that show good cycle characteristics in a higher voltage range is underway.

[0003] For example, Patent Document 1 describes a positive electrode active material for a non-aqueous electrolyte secondary battery containing secondary particles formed by a collection of multiple primary particles, which is considered to exhibit good charge and discharge cycle characteristics at high voltage. For the positive electrode active material for a non-aqueous electrolyte secondary battery described in Patent Document 1, an oxide containing lithium, aluminum and boron is formed on the surface of the secondary particles, and aluminum is contained at a higher concentration than the parent phase of the primary particles at the grain boundaries between the primary particles near the surface of the secondary particles.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-76336 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In the non-aqueous electrolyte secondary battery positive electrode active material described in patent document 1, in order to further improve the charge and discharge cycle characteristics under high voltage, it is necessary to add a relatively large amount of aluminum compounds. In this way, there is a problem of reduced charge and discharge capacity. Therefore, the object of the present invention is to provide a non-aqueous electrolyte secondary battery positive electrode active material that can constitute a non-aqueous electrolyte secondary battery that reduces the capacity reduction caused by additives and has good cycle characteristics under high voltage.

[0009] Solutions to the problem

[0010] The first mode is a positive electrode active material for a non-aqueous electrolyte secondary battery, which has a layered structure and includes lithium transition metal composite oxide particles containing nickel, and oxides containing lithium and aluminum and oxides containing lithium and boron attached to the surface of the lithium transition metal composite oxide particles. The lithium transition metal composite oxide particles contain secondary particles formed by agglomeration of primary particles in which aluminum is solid-dissolved in the surface layer. For the lithium transition metal composite oxide particles, the difference between the ratio of the number of moles of aluminum solid-dissolved in the surface layer of the primary particles in the composition of the lithium transition metal composite oxide particles to the total number of moles of metals other than lithium and the ratio of the number of moles of aluminum present in the region other than the surface layer of the primary particles in the composition of the lithium transition metal composite oxide particles to the total number of moles of metals other than lithium is greater than 0.22 mol% and less than 0.6 mol%.

[0011] The second method is a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, the method comprising: preparing a mixture of lithium transition metal composite oxide particles having a layered structure and containing nickel, a lithium compound, an aluminum compound, and a boron compound; and heat treating the prepared mixture. The lithium transition metal composite oxide particles contain secondary particles formed by agglomeration of primary particles. The aluminum compound uses an aluminum compound in which the total volume ratio of particles with a particle size of 0.4 μm or more and 3.0 μm or less in a volume-based particle size distribution is greater than 54%.

[0012] Effects of the Invention

[0013] According to the present invention, it is possible to provide a positive electrode active material for a nonaqueous electrolyte secondary battery that can constitute a nonaqueous electrolyte secondary battery with excellent cycle characteristics at a high voltage and with reduced capacity reduction due to additives. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1A This is a scanning electron microscope (SEM) image of the aluminum oxide used in Example 1.

[0015] Figure 1B This is a SEM image of the aluminum hydroxide used in Example 2.

[0016] Figure 1C This is a SEM image of the aluminum oxide used in Comparative Example 1.

[0017] Figure 1D This is a SEM image of the aluminum oxide used in Comparative Example 2.

[0018] Figure 2 This is the particle size distribution of the aluminum compound used in Examples 1 and 2 and Comparative Example 2.

[0019] Figure 3The figure shows the measurement positions of elemental analysis in the reflection electron microscope image of the cross section of the positive electrode active material.

[0020] Figure 4 This is a diagram showing the results of elemental analysis in the surface layer of primary particles of the positive electrode active material.

[0021] Figure 5 This is the particle size distribution of the aluminum-containing oxide attached to the surface of the positive electrode active material obtained in Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0022] In this specification, the term "process" is not only an independent process, but also included in this term as long as the desired purpose of the process can be achieved when it cannot be clearly distinguished from other processes. In addition, the content of each component in the composition refers to the total amount of the multiple substances present in the composition, unless otherwise specified, when there are multiple substances equivalent to each component in the composition. Hereinafter, embodiments of the present invention will be described in detail. However, the embodiments shown below illustrate positive active materials for non-aqueous electrolyte secondary batteries and methods for making the same, etc., which are used to concretize the technical ideas of the present invention, and the present invention is not limited to the positive active materials for non-aqueous electrolyte secondary batteries and methods for making the same, etc. shown below.

[0023] Positive electrode active material for non-aqueous electrolyte secondary battery

[0024] The positive electrode active material for a non-aqueous electrolyte secondary battery (hereinafter also referred to as "positive electrode active material") has a layered structure and includes lithium transition metal composite oxide particles containing nickel, and oxides containing lithium and aluminum and oxides containing lithium and boron attached to the surface of the lithium transition metal composite oxide particles. The lithium transition metal composite oxide particles contain secondary particles formed by the aggregation of primary particles in which aluminum is solid-dissolved in the surface layer. With respect to the lithium transition metal composite oxide particles, the difference between the ratio of the number of moles of aluminum solid-dissolved in the surface layer of the primary particles in the composition of the lithium transition metal composite oxide particles to the total number of moles of metals other than lithium and the ratio of the number of moles of aluminum present in the region other than the surface layer of the primary particles to the total number of moles of metals other than lithium is greater than 0.22 mol% and less than 0.6 mol%.

[0025] A non-aqueous electrolyte secondary battery using a positive electrode active material composed of an oxide containing lithium and aluminum and an oxide containing lithium and boron attached to the surface of secondary particles formed by primary particles with aluminum solid dissolved in the surface can show excellent cycle characteristics. This can be considered, for example, as described below. It is believed that in the secondary particles formed by the aggregation of multiple primary particles, the crystal structure of the surface of the primary particles begins to deteriorate during the charge and discharge cycle. It is believed that in contrast, since aluminum is solid dissolved in the surface of the primary particles, structural degradation can be suppressed. In addition, it is believed that under high voltage conditions, hydrofluoric acid is sometimes generated, the constituent components of the surface of the primary particles are dissolved, and the effect of aluminum solid dissolved in the surface of the primary particles is sometimes reduced. However, it is believed that by attaching an oxide containing lithium and aluminum and an oxide containing lithium and boron on the surface of the secondary particles, the influence caused by hydrofluoric acid can be suppressed, and the effect of aluminum solid dissolved in the surface of the primary particles is fully exerted, and excellent cycle characteristics can be achieved. In addition, the nickel contained in the lithium transition metal composite oxide is easily reduced when it is a high valence number. Therefore, it is believed that the lithium transition metal composite oxide containing nickel is prone to the destruction of the crystal structure accompanying the cycle process. Therefore, it is considered that the present embodiment is particularly effective in stabilizing the structure of the lithium transition metal composite oxide containing nickel.

[0026] The primary particles have a layered structure and are composed of a lithium transition metal composite oxide containing nickel (hereinafter also referred to as "lithium transition metal composite oxide"). The lithium transition metal composite oxide contains at least lithium (Li), nickel (Ni) and aluminum (Al) dissolved in the surface layer, but may further contain at least one of cobalt (Co) and manganese (Mn). In addition, in addition to these, the lithium transition metal composite oxide may further contain at least one first metal element selected from zirconium (Zr), titanium (Ti), magnesium (Mg), tantalum (Ta), niobium (Nb) and molybdenum (Mo). In addition to aluminum dissolved in the surface layer, the lithium transition metal composite oxide may also contain aluminum as the first metal element. That is, the first metal element may be at least one selected from aluminum (Al), zirconium (Zr), titanium (Ti), magnesium (Mg), tantalum (Ta), niobium (Nb) and molybdenum (Mo).

[0027] In the lithium transition metal composite oxide, the molar ratio of nickel to the total molar number of metals other than lithium is, for example, 0.33 or more, preferably 0.4 or more, and more preferably 0.55 or more. In addition, the upper limit of the molar ratio of nickel to the total molar number of metals other than lithium is, for example, less than 1, preferably less than 0.95, more preferably less than 0.8, and further preferably less than 0.6. When the molar ratio of nickel is the above-mentioned range, in the non-aqueous electrolyte secondary battery, it is possible to achieve a balance between the charge and discharge capacity at high voltage and the cycle characteristics.

[0028] In the case where the lithium transition metal composite oxide contains cobalt, the molar ratio of cobalt to the total molar number of metals other than lithium is, for example, 0.02 or more, preferably 0.05 or more, more preferably 0.1 or more, and further preferably 0.15 or more. In addition, the upper limit of the molar ratio of cobalt to the total molar number of metals other than lithium is, for example, less than 1, preferably less than 0.33, more preferably less than 0.3, and further preferably less than 0.25. When the molar ratio of cobalt is 0.02 or more and less than 1, in a non-aqueous electrolyte secondary battery, a sufficient charge and discharge capacity at high voltage can be achieved.

[0029] In the case where the lithium transition metal composite oxide contains manganese, the molar ratio of manganese to the total molar number of metals other than lithium is, for example, 0.01 or more, preferably 0.05 or more, more preferably 0.1 or more, and further preferably 0.15 or more. In addition, the upper limit of the molar ratio of manganese to the total molar number of metals other than lithium is, for example, 0.33 or less, preferably 0.3 or less, and more preferably 0.25 or less. When the content ratio of manganese is within the range of 0.01 or more and 0.33 or less, in a non-aqueous electrolyte secondary battery, it is possible to achieve a balance between charge and discharge capacity and safety.

[0030] When the lithium transition metal composite oxide contains the first metal element, the molar ratio of the first metal element to the total molar number of metals other than lithium is, for example, 0.001 or more, preferably 0.002 or more. In addition, the upper limit of the molar ratio of the first metal element to the total molar number of metals other than lithium is, for example, 0.02 or less, preferably 0.015 or less.

[0031] In the lithium transition metal composite oxide, the molar ratio of lithium to the total molar number of metals other than lithium is, for example, 1.0 or more, preferably 1.03 or more, and more preferably 1.05 or more. In addition, the upper limit of the molar ratio of lithium to the total molar number of metals other than lithium is, for example, 1.5 or less, and preferably 1.25 or less.

[0032] When the lithium transition metal composite oxide contains cobalt and manganese in addition to nickel, the molar ratio of nickel, cobalt and manganese is, for example, nickel:cobalt:manganese = (0.33-0.95):(0.02-0.33):(0.01-0.33), preferably (0.55-0.6):(0.15-0.25):(0.15-0.3).

[0033] The lithium transition metal composite oxide contains aluminum dissolved in a surface layer, for example, and may have a composition represented by the following formula (1) or (1a).

[0034] Li a Ni 1-x-y Co x Mn yAl z M 1 w O2 (1)

[0035] Where, 1.0≤a≤1.5, 0.02≤x≤0.34, 0.01≤y≤0.34, 0.002≤z≤0.05, 0≤w≤0.02, 0.05≤x+y≤0.67, M 1 It is at least one selected from Zr, Ti, Mg, Ta, Nb and Mo. In addition, it may be 0.0022<z≤0.05, 0.0022<z<0.006, 0.003≤z≤0.005, or 0.0035≤z≤0.0045. Furthermore, it may be 0.02≤x≤0.33, 0.01≤y≤0.33, or 0.05≤x+y≤0.66.

[0036] Li a Ni b Co c Mn d Al e M 1 f O2 (1a)

[0037] Where, 1.0≤a≤1.5, 0.33≤b≤0.95, 0.02≤c≤0.33, 0.01≤d≤0.33, 0.0022 <e≤0.05,0≤f≤0.02,b+c+d=1,M 1 It is at least one selected from Zr, Ti, Mg, Ta, Nb and Mo.

[0038] Aluminum is solid-dissolved in the surface layer of the primary particles constituting the lithium transition metal composite oxide particles. Here, the surface layer refers to a depth region from the surface of the primary particle to 100 nm, preferably 70 nm. The particle size of the primary particle is measured as follows: for example, the area of ​​the primary particle is calculated based on the contour confirmed by observation using a scanning electron microscope (SEM), and the particle size is measured in the form of an equivalent circle diameter of the area. The average particle size of the primary particles is, for example, greater than 0.3 μm and less than 2.0 μm, preferably greater than 0.6 μm and less than 1.5 μm. The average particle size of the primary particles is calculated, for example, as the arithmetic mean of the particle sizes of 100 primary particles measured by SEM observation.

[0039] The state of aluminum solid solution in the surface layer of the primary particle can be observed by energy dispersive X-ray analysis (EDX). For example, in the cross section of the secondary particle, by analyzing the composition of the constituent elements at the contact portion of the primary particles, that is, the grain boundary, the aluminum content in the surface layer of the primary particle can be determined. If the aluminum content at the grain boundary is sufficiently greater than the aluminum content near the center of the primary particle, it can be said that aluminum is solid dissolved in the surface layer of the primary particle. Aluminum can be solid dissolved in the entire interface between the primary particles, or it can be solid dissolved locally.

[0040] For the amount of aluminum dissolved in the surface layer of the primary particle, in the composition of the lithium transition metal composite oxide, the difference between the ratio of the molar number of aluminum dissolved in the surface layer of the primary particle to the total molar number of metals other than lithium and the molar number of aluminum present in the region other than the surface layer of the primary particle to the total molar number of metals other than lithium is, for example, in the range of 0.2 mol% or more and less than 0.6 mol%, preferably 0.3 mol% or more and 0.5 mol% or less, more preferably 0.35 mol% or more and 0.45 mol% or less. The above-mentioned amount of aluminum dissolved in the surface layer can be, for example, in the range of greater than 0.22 mol% and less than 0.6 mol%, can be 0.25 mol% or more, 0.3 mol% or more, or 0.35 mol% or more, can be 0.5 mol% or less, or 0.45 mol% or less. Here, the aluminum present in the region other than the surface layer of the primary particle contains aluminum contained in the composition of the lithium transition metal composite oxide as the matrix material before the aluminum is dissolved in the surface layer.

[0041] The amount of aluminum dissolved in the surface layer of the primary particle can be measured as follows, using aluminum as an amphoteric element. The oxide containing lithium and aluminum attached to the surface of the positive electrode active material can be cleaned and removed with an alkaline aqueous solution such as an aqueous sodium hydroxide solution, and then the aluminum content is quantitatively measured using an inductively coupled plasma (ICP) emission analyzer. Here, when the lithium transition metal composite oxide that becomes the base material contains aluminum in the composition, that is, when the area other than the surface layer of the primary particle contains aluminum, the aluminum content contained in the composition of the lithium transition metal composite oxide that becomes the base material is subtracted, so that the amount of aluminum dissolved in the surface layer of the primary particle can be calculated.

[0042] The secondary particles of the lithium transition metal composite oxide particles are formed in the form of aggregates of the primary particles. The average particle size of the secondary particles is, for example, 2 μm or more and 25 μm or less, preferably 3 μm or more and 17 μm or less. The average particle size of the secondary particles is measured as a particle size at which the volume cumulative value from the small particle size side becomes 50% in the volume-based particle size distribution obtained by the laser scattering method.

[0043] The oxide containing lithium and aluminum and the oxide containing lithium and boron adhere to the surface of the secondary particle. The oxide containing lithium and aluminum and the oxide containing lithium and boron may adhere to at least a part of the surface of the secondary particle.

[0044] In the positive electrode active material, the content of the oxide containing lithium and aluminum relative to the lithium transition metal composite oxide particles is converted to the total molar number of aluminum relative to the metal other than lithium in the lithium transition metal composite oxide particles, for example, 0.1 mol% or more and 0.8 mol% or less, preferably 0.13 mol% or more, more preferably 0.15 mol% or more, and preferably 0.5 mol% or less, more preferably 0.25 mol% or less. When the content of the oxide containing lithium and aluminum is in the range of 0.1 mol% or more and 0.8 mol% or less, there is a tendency to suppress the decrease in charge and discharge capacity and further improve the cycle characteristics at high voltage.

[0045] In the volume-based particle size distribution of the oxide containing lithium and aluminum attached to the surface of the lithium transition metal composite oxide particle, the total volume ratio of particles with a particle size of 0.4 μm or more and 3.0 μm or less is, for example, 50% or more, preferably 70% or more or 90% or more. Here, the total volume ratio is the cumulative volume ratio of particles with a particle size of 0.4 μm or more and 3.0 μm or less relative to the total volume of the oxide particles containing lithium and aluminum.

[0046] In the positive electrode active material, the content of the oxide containing lithium and boron relative to the lithium transition metal composite oxide particles is converted to the total molar number of boron relative to the metal other than lithium in the lithium transition metal composite oxide particles, for example, 0.3 mol% or more and 2.0 mol% or less, preferably 0.4 mol% or more, more preferably 0.45 mol% or more, and preferably 1.0 mol% or less, more preferably 0.6 mol% or less. It is believed that the role of boron is, for example, to transport aluminum to the interior of the secondary particles through the grain boundaries between the primary particles. Therefore, when the content of the oxide containing lithium and boron relative to the lithium transition metal composite oxide particles is within the above range, there is a tendency to suppress the reduction in charge and discharge capacity and further improve the cycle characteristics at high voltage.

[0047] The total amount of aluminum solid solution in the positive electrode active material, the amount of oxide containing lithium and aluminum attached, and the amount of oxide containing lithium and boron attached is converted to the total molar number of aluminum or boron relative to the metal other than lithium in the lithium transition metal composite oxide particles, and is, for example, 3.4 mol% or less, preferably 2.0 mol% or less, and, for example, 0.6 mol% or more, preferably 0.83 mol% or more.

[0048] In the positive electrode active material, the content ratio (Al / B) of the oxide containing lithium and aluminum relative to the oxide containing lithium and boron is, for example, 0.05 or more and 2.7 or less, preferably 0.5 or more and 2.0 or less, and more preferably 0.8 or more and 1.5 or less. The above content ratio (Al / B) may be 0.1 or more, 0.2 or more, or 0.3 or more, and may be 1 or less, 0.8 or less, or 0.6 or less. When the content ratio is within the above range, there is a tendency to suppress the reduction of the charge and discharge capacity and further improve the cycle characteristics at high voltage.

[0049] In the positive electrode active material, the ratio of the amount of aluminum solid solution in the surface layer of the primary particles to the total content of aluminum, that is, the aluminum solid solution rate (%) is, for example, greater than 40% and less than 100%, preferably greater than 50% and less than 90%, and more preferably greater than 60% and less than 80%. When the aluminum solid solution rate is within the above range, there is a tendency to suppress the decrease in charge and discharge capacity and further improve the cycle characteristics at high voltage. Here, the total content of aluminum in the positive electrode active material is set to the sum of the amount of aluminum contained in the oxide containing lithium and aluminum attached to the surface of the secondary particles and the amount of aluminum solid dissolved in the surface layer of the primary particles. It should be noted that the total content of aluminum in the positive electrode active material can be quantified using an inductively coupled plasma (ICP) emission spectrometer.

[0050] In the positive electrode active material, the ratio of the amount of aluminum contained in the oxide containing lithium and aluminum attached to the surface of the secondary particles to the total content of aluminum, that is, the aluminum coverage (%) is, for example, greater than 0% and less than 60%, preferably greater than 10% and less than 50%, and more preferably greater than 20% and less than 40%. When the aluminum coverage is within the above range, there is a tendency to suppress the decrease in charge and discharge capacity and further improve the cycle characteristics at high voltage.

[0051] Method for producing positive electrode active material for non-aqueous electrolyte secondary battery

[0052] The method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery includes: a preparation step of preparing a mixture having a layered structure and containing lithium transition metal composite oxide particles containing nickel, a lithium compound, an aluminum compound, and a boron compound; and a heat treatment step of heat-treating the prepared mixture. The lithium transition metal composite oxide particles contain secondary particles formed by agglomeration of primary particles. In addition, an aluminum compound is used in which the ratio of particles with a particle size of 0.4 μm or more and 3.0 μm or less in the volume-based particle size distribution of the aluminum compound is greater than 54%. The method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery is a method for efficiently manufacturing the above-mentioned positive electrode active material.

[0053] By adding an aluminum compound to lithium transition metal composite oxide particles containing secondary particles formed by agglomeration of primary particles and performing heat treatment, aluminum can be diffused from the surface of the secondary particles through the grain boundaries to the inside of the secondary particles. At this time, by using an aluminum compound with a specific particle size distribution, aluminum can be solid-dissolved in the surface layer of the primary particles with a small amount of addition, and a positive electrode active material containing an oxide of aluminum attached to the surface of the secondary particles can be efficiently manufactured. The non-aqueous electrolyte secondary battery composed of the obtained positive electrode active material can achieve good charge and discharge cycle characteristics under high voltage. It is believed that this is because, for example, the smaller the particle size of the aluminum compound, the more the diffusion amount of aluminum into the inside of the secondary particles increases.

[0054] In the preparation step, a mixture of lithium transition metal composite oxide particles having a layered structure and containing nickel, a lithium compound, an aluminum compound, and a boron compound is prepared. The preparation step may include: a base material preparation step of preparing lithium transition metal composite oxide particles to be a base material; and a mixing step of mixing the lithium transition metal composite oxide particles, the lithium compound, the aluminum compound, and the boron compound to obtain a mixture.

[0055] In the matrix preparation step, lithium transition metal composite oxide particles having a layered structure and containing nickel are prepared. The lithium transition metal composite oxide particles serving as the matrix can be appropriately selected from commercially available products, or can be prepared by preparing a composite oxide having a desired composition and heat-treating it together with a lithium compound to prepare lithium transition metal composite oxide particles.

[0056] As methods for obtaining composite oxides having a desired composition, there can be cited: a method of mixing raw material compounds (hydroxides, carbon oxides, etc.) according to a target composition and decomposing them into composite oxides by heat treatment; a method of dissolving a raw material compound soluble in a solvent in a solvent, obtaining a precursor precipitate according to the target composition by temperature adjustment, pH adjustment, complexing agent addition, etc., and obtaining a composite oxide by heat treatment of these precursors. An example of a method for producing a base material is described below.

[0057] The method for obtaining a composite oxide by coprecipitation may include: adjusting the pH of a mixed aqueous solution containing metal ions to a desired composition, etc., to obtain a seed crystal generation step; growing the generated seed crystal to obtain a composite hydroxide having desired characteristics; and heat treating the obtained composite hydroxide to obtain a composite oxide step. For details of the method for obtaining a composite oxide, reference may be made to Japanese Patent Application Publication No. 2003-292322, Japanese Patent Application Publication No. 2011-116580 (US Patent Application Publication No. 2012 / 270107 Specification), etc.

[0058] In the seed crystal generation process, a liquid medium containing seed crystals is obtained by adjusting the pH of a mixed solution containing nickel ions in a desired composition, for example, from 11 to 13. The seed crystal may contain, for example, nickel hydroxide. The mixed solution can be prepared by dissolving a nickel salt and a manganese salt and a cobalt salt contained as required in water in a desired proportion. Examples of nickel salts, manganese salts, and cobalt salts include sulfates, nitrates, and hydrochlorides. In addition to nickel salts, manganese salts, and cobalt salts, the mixed solution may contain other metal salts as required. The temperature in the reaction tank in the seed crystal generation process may be set to, for example, 40°C to 80°C. The atmosphere in the seed crystal generation process may be set to a low oxidizing atmosphere, for example, preferably maintaining an oxygen concentration of less than 10% by volume.

[0059] In the crystallization step, the generated seed crystals are grown to obtain a precipitate containing nickel having the desired properties. The growth of the seed crystals can be carried out, for example, by adding a mixed solution containing nickel ions to a liquid medium containing the seed crystals while maintaining its pH at, for example, 7 to 12.5, preferably 7.5 to 12. The addition time of the mixed solution is, for example, 1 hour to 24 hours, preferably 3 hours to 18 hours. The temperature in the crystallization step can be, for example, set to 40°C to 80°C. The atmosphere in the crystallization step is the same as that in the seed crystal generation step.

[0060] The pH adjustment in the seed crystal forming step and the crystallization step can be performed using an acidic aqueous solution such as an aqueous sulfuric acid solution or an aqueous nitric acid solution, or an alkaline aqueous solution such as an aqueous sodium hydroxide solution or an aqueous ammonia solution.

[0061] In the process of obtaining the composite oxide, the composite oxide is obtained by heat treating the composite hydroxide obtained in the crystallization process. The heat treatment can be carried out, for example, by heating at a temperature of 500°C or less, preferably by heating at 350°C or less. Moreover, the temperature of the heat treatment is, for example, above 100°C, preferably above 200°C, and the time of the heat treatment can be, for example, 0.5 hours to 48 hours, preferably 5 hours to 24 hours. The atmosphere of the heat treatment can be in the air or in an atmosphere containing oxygen. The heat treatment can be carried out using, for example, a box furnace, a rotary kiln furnace, a pusher furnace, a roller kiln, etc.

[0062] Next, a mixture containing lithium (hereinafter also referred to as a lithium mixture) obtained by mixing the obtained composite oxide with a lithium compound is heat-treated at a temperature of 550° C. to 1000° C. to obtain a heat-treated product. The obtained heat-treated product has a layered structure and contains a lithium transition metal oxide containing nickel.

[0063] Examples of the lithium compound to be mixed with the composite oxide include lithium hydroxide, lithium carbonate, lithium oxide, etc. The particle size of the lithium compound to be mixed is, for example, 0.1 μm to 100 μm, preferably 2 μm to 20 μm, in terms of 50% particle size of cumulative particle size distribution based on volume.

[0064] In the lithium mixture, the ratio of the total molar number of lithium to the total molar number of metal elements constituting the composite oxide is, for example, 1 to 1.5, preferably 1.03 to 1.25. The composite oxide and the lithium compound can be mixed using, for example, a high-speed shear mixer.

[0065] The lithium mixture may further contain other metals except lithium, nickel, manganese and cobalt. As other metals, Al, Zr, Ti, Mg, Ta, Nb, Mo etc. can be listed, preferably at least one selected from these elements. In the case where the lithium mixture contains other metals, other metal simple substances or metal compounds can be mixed with composite oxides and lithium compounds to obtain a mixture. As metal compounds containing other metals, oxides, hydroxides, chlorides, nitrides, carbonates, sulfates, nitrates, acetates, oxalates etc. can be listed.

[0066] When the lithium mixture contains other metals, the ratio of the total molar number of the metal elements constituting the composite oxide to the total molar number of the other metals is, for example, 1:0.001 to 1:0.02, and preferably 1:0.002 to 1:0.015.

[0067] The heat treatment temperature of the lithium mixture is preferably, for example, 600° C. or higher and 1000° C. or lower. The heat treatment of the lithium mixture can be performed at a single temperature, but in order to suppress the growth of particles caused by sintering and maintain the desired particle shape, it can be performed multiple times before the heat treatment at the highest temperature at a heat treatment temperature lower than the highest temperature. The heat treatment time is, for example, 0.5 hours to 48 hours, and when the heat treatment is performed at multiple temperatures, it can be set to 0.2 hours to 47 hours respectively.

[0068] The atmosphere for the heat treatment may be air or an atmosphere containing oxygen. The heat treatment may be performed using, for example, a box furnace, a rotary kiln, a pusher furnace, a roller hearth furnace, or the like.

[0069] For the lithium transition metal composite oxide that serves as the base material, the ratio of the molar number of nickel to the total molar number of metals other than lithium is, for example, greater than 0.33, preferably greater than 0.4, more preferably greater than 0.55, and the upper limit is, for example, less than 1, preferably less than 0.95, more preferably less than 0.8, and further preferably less than 0.6.

[0070] When the lithium transition metal composite oxide serving as the base material contains cobalt, the molar ratio of cobalt to the total molar number of metals other than lithium is, for example, greater than 0.02, preferably greater than 0.05, more preferably greater than 0.1, and further preferably greater than 0.15, and the upper limit is, for example, less than 1, preferably less than 0.33, more preferably less than 0.3, and further preferably less than 0.25.

[0071] When the lithium transition metal composite oxide serving as the base material contains manganese, the molar ratio of manganese to the total molar number of metals other than lithium is, for example, greater than 0.01, preferably greater than 0.05, more preferably greater than 0.1, and further preferably greater than 0.15, and the upper limit is, for example, less than 0.33, preferably less than 0.3, and more preferably less than 0.25.

[0072] When the lithium transition metal composite oxide serving as the base material contains cobalt and manganese in addition to nickel, the molar ratio of nickel, cobalt and manganese is, for example, nickel:cobalt:manganese = (0.33~0.95):(0.02~0.33):(0.01~0.33), preferably (0.55~0.6):(0.15~0.25):(0.15~0.3).

[0073] The lithium transition metal composite oxide serving as the base material may have a composition represented by, for example, the following formula (2) or (2a).

[0074] Li a Ni 1-x-y Co x Mn y Al v M 1 w O2 (2)

[0075] Where, 1.0≤a≤1.5, 0.02≤x≤0.34, 0.01≤y≤0.34, 0≤v≤0.048, 0≤w≤0.02, 0.05≤x+y≤0.67, M 1 It is at least one selected from Zr, Ti, Mg, Ta, Nb and Mo.

[0076] Herein, x may be less than or equal to 0.33, y may be less than or equal to 0.33, and x+y may be less than or equal to 0.66.

[0077] Li a Ni p Co q Mn r M 1 s O2 (2a)

[0078] Where, 1.0≤a≤1.5, 0.33≤p≤0.95, 0.02≤q≤0.33, 0.01≤r≤0.33, 0≤s≤0.02, p+q+r=1, M 1 It is at least one selected from Al, Zr, Ti, Mg, Ta, Nb and Mo.

[0079] The volume average particle size of the base material is, for example, 2 μm or more and 25 μm or less, and preferably 3 μm or more and 17 μm or less.

[0080] In the mixing step, the lithium transition metal composite oxide particles, which are the matrix materials, the lithium compound, the aluminum compound, and the boron compound are mixed to obtain a mixture. As a mixing method, for example, dry mixing using a high-speed shear mixer or the like is used.

[0081] As lithium compounds, for example, lithium hydroxide, lithium carbonate, lithium nitrate, etc. can be cited. The volume average particle size of the lithium compound is, for example, 0.1 μm or more and 100 μm or less, preferably 1 μm or more and 50 μm or less. In the mixture, the mixing ratio of the lithium compound to the lithium transition metal composite oxide particles is, for example, 1.2 mol% or more and 7.4 mol% or less, preferably 1.45 mol% or more and 4 mol% or less in terms of lithium conversion. The mixing ratio converted to lithium can be 1.6 mol% or more, 1.8 mol% or more, or 2 mol% or more, and can be 3 mol% or less, 2.6 mol% or less, or 2.4 mol% or less.

[0082] As aluminum compounds, for example, aluminum oxide, aluminum hydroxide, etc. can be cited. As aluminum compounds, an aluminum compound having a particle size distribution of, for example, more than 54% in which the total volume ratio of particles with a particle size of 0.4 μm or more and 3.0 μm or less in a volume-based particle size distribution is used, and preferably an aluminum compound having a particle size distribution of more than 80% and more preferably more than 90% in which the total volume ratio is used. Here, the total volume ratio is the volume cumulative value of particles with a particle size of 0.4 μm or more and 3.0 μm or less in the particle size distribution. When the particle size distribution of the aluminum compound is within the above range, there is a tendency to suppress the decrease in charge and discharge capacity and further improve the cycle characteristics at high voltage. In the mixture, the mixing ratio of the aluminum compound to the lithium transition metal composite oxide particles is, for example, 0.1 mol% or more and 0.8 mol% or less in terms of aluminum, preferably 0.13 mol% or more and 0.5 mol% or less. The mixing ratio in terms of aluminum may be 0.2 mol % or more, 0.4 mol % or more, or 0.5 mol % or more, and may be 1.2 mol % or less, 1 mol % or less, or 0.7 mol % or less.

[0083] As the boron compound, for example, boric acid (orthoboric acid) and boron oxide can be cited. The volume average particle size of the boron compound is, for example, 0.1 μm or more and 100 μm or less, preferably 1 μm or more and 50 μm or less. In the mixture, the mixing ratio of the boron compound to the lithium transition metal composite oxide particles is, for example, 0.3 mol% or more and 2 mol% or less in terms of boron conversion, preferably 0.4 mol% or more and 1 mol% or less. The mixing ratio converted by boron can be 0.8 mol% or less, or 0.6 mol% or less.

[0084] In the heat treatment process, the prepared mixture is heat treated to obtain a positive electrode active material for a non-aqueous electrolyte secondary battery as a heat-treated product. The temperature of the heat treatment is, for example, 500°C or more and 800°C or less, preferably 550°C or more, more preferably 600°C or more, and preferably 750°C or less. The heat treatment can be carried out by putting the prepared mixture into a given temperature environment, or by heating the prepared mixture from, for example, room temperature to a given temperature and maintaining the temperature for a given time. In the case of heating for heat treatment, the heating rate can be, for example, 1°C / min or more and 20°C / min or less. The time of the heat treatment is, for example, 2 hours or more and 40 hours or less, preferably 5 hours or more and 20 hours or less.

[0085] The atmosphere for the heat treatment may be air or an atmosphere containing oxygen. The heat treatment may be performed using, for example, a box furnace, a rotary kiln, a pusher furnace, a roller hearth furnace, or the like.

[0086] Preferably, in the volume-based particle size distribution of the oxide containing lithium and aluminum attached to the surface of the lithium transition metal composite oxide particles after the heat treatment, the total volume ratio of particles with a particle size of 0.4 μm or more and 3.0 μm or less is greater than 50%. When the particle size distribution of the oxide containing lithium and aluminum is within the above range, the dissolution of the constituent components of the surface layer of the primary particles caused by hydrofluoric acid or the like can be suppressed, and the effect of aluminum dissolved in the surface layer of the primary particles can be fully exerted, and excellent cycle characteristics can be achieved.

[0087] In the method for producing the positive electrode active material, the heat-treated product obtained after the heat treatment may be subjected to a pulverization treatment, or may be further subjected to a dispersion treatment, a classification treatment, or the like.

[0088] Positive electrode for non-aqueous electrolyte secondary battery

[0089] The positive electrode for a non-aqueous electrolyte secondary battery comprises a current collector and a positive electrode active material layer disposed on the current collector and containing the positive electrode active material for a non-aqueous electrolyte secondary battery. A non-aqueous electrolyte secondary battery having the positive electrode has excellent charge-discharge cycle characteristics at high voltage.

[0090] The material of the current collector may be, for example, aluminum, nickel, stainless steel, etc. The positive electrode active material layer may be formed by coating the positive electrode mixture obtained by mixing the positive electrode active material, conductive material, binder, etc. with a solvent on the current collector, and performing drying treatment, pressurization treatment, etc. The conductive material may be, for example, natural graphite, artificial graphite, acetylene black, etc. The binder may be, for example, polyvinylidene fluoride, polytetrafluoroethylene, polyamide acrylic resin, etc.

[0091] Non-aqueous electrolyte secondary battery

[0092] The nonaqueous electrolyte secondary battery is provided with the above-mentioned nonaqueous electrolyte secondary battery positive electrode. The nonaqueous electrolyte secondary battery is provided with a nonaqueous secondary battery negative electrode, a nonaqueous electrolyte, a separator, etc. in addition to the nonaqueous electrolyte secondary battery positive electrode. Regarding the negative electrode, nonaqueous electrolyte, separator, etc. in the nonaqueous electrolyte secondary battery, it is possible to appropriately select the negative electrode, nonaqueous electrolyte, separator, etc. for the nonaqueous electrolyte secondary battery recorded in, for example, Japanese Patent Publication No. 2002-075367, Japanese Patent Publication No. 2011-146390, Japanese Patent Publication No. 2006-12433, etc. and use them.

[0093] Example

[0094] The present invention is described in more detail below by way of examples, but the present invention is not limited to these examples. It should be noted that the volume average particle size of the lithium transition metal composite oxide particles uses a value where the volume cumulative value from the small particle size side in the volume-based particle size distribution obtained by the laser scattering method becomes 50%. Specifically, the volume average particle size is measured using a laser diffraction particle size distribution device (MALVERN Inst. MASTERSIZER 2000).

[0095] [Example 1]

[0096] Prepare pure water in a stirred state in a reaction tank, and add aqueous solutions of nickel sulfate, cobalt sulfate, and manganese sulfate at a flow ratio of Ni:Co:Mn=6:2:2 in a molar ratio of nickel, cobalt, and manganese. After the addition is completed, the liquid temperature is set to 50°C, and a given amount of sodium hydroxide aqueous solution is added to obtain a precipitate of nickel-cobalt-manganese composite hydroxide. The obtained precipitate is washed with water, filtered, and separated, and lithium carbonate and zirconium (IV) oxide are mixed in a manner of Li:(Ni+Co+Mn):Zr=1.02:1:0.005 (molar ratio) to obtain a raw material mixture. The obtained raw material mixture is calcined at 840°C in an air atmosphere for 12 hours to obtain a sintered body. The obtained sintered body is crushed and passed through a dry sieve to obtain a composition formula Li 1.07 Ni 0.6 Co 0.2 Mn 0.2 Zr0.005 The lithium transition metal composite oxide particles serving as the matrix are represented by O2. The volume average particle size of the obtained lithium transition metal composite oxide particles serving as the matrix was 11 μm.

[0097] The lithium transition metal composite oxide obtained above, lithium hydroxide as a lithium compound, aluminum oxide as an aluminum compound, and boric acid (orthoboric acid, H3BO3) as a boron compound were mixed in a high-speed shear mixer in such a manner that the ratio of each element of lithium: aluminum: boron to the lithium transition metal composite oxide was 2.1 mol%: 0.6 mol%: 0.5 mol% to obtain a mixture. The volume average particle size of the aluminum oxide as an aluminum compound was 1.1 μm. The obtained mixture was calcined at 700° C. for 10 hours in the atmosphere, thereby obtaining the positive electrode active material E1 of Example 1.

[0098] In the volume-based particle size distribution of the aluminum compound used in Example 1, the total volume ratio of particles having a particle size of 0.4 μm or more and 3.0 μm or less was 97%. The SEM image of the aluminum compound used in Example 1 is shown in FIG. Figure 1A , the particle size distribution is shown in Figure 2 .

[0099] [Example 2]

[0100] A positive electrode active material E2 of Example 2 was obtained in the same manner as in Example 1 except that aluminum hydroxide was used as the aluminum compound. The volume average particle size of the aluminum hydroxide was 1.7 μm.

[0101] In the volume-based particle size distribution of the aluminum compound used in Example 2, the total volume ratio of particles having a particle size of 0.4 μm or more and 3.0 μm or less was 91%. The SEM image of the aluminum compound used in Example 2 is shown in FIG. Figure 1B , the particle size distribution is shown in Figure 2 .

[0102] [Comparative Example 1]

[0103] Positive electrode active material C1 of Comparative Example 1 was obtained in the same manner as in Example 1 except that alumina having a volume average particle size of 40 nm was used as the aluminum compound.

[0104] In the volume-based particle size distribution of the aluminum compound used in Comparative Example 1, the total volume ratio of particles having a particle size of 0.4 μm or more and 3.0 μm or less was 0%. The SEM image of the aluminum compound used in Comparative Example 1 is shown in FIG. Figure 1C .

[0105] [Comparative Example 2]

[0106] A positive electrode active material C2 of Comparative Example 2 was obtained in the same manner as in Example 1 except that alumina having a volume average particle size of 2.9 μm was used as the aluminum compound.

[0107] In the volume-based particle size distribution of the aluminum compound used in Comparative Example 2, the total volume ratio of particles having a particle size of 0.4 μm or more and 3.0 μm or less was 54%. The SEM image of the aluminum compound used in Comparative Example 2 is shown in FIG. Figure 1D , the particle size distribution is shown in Figure 2 .

[0108] [Comparative Example 3]

[0109] The lithium-transition metal composite oxide particles used as the matrix material obtained in Example 1 were used as the positive electrode active material C3 of Comparative Example 3.

[0110] <Evaluation of aluminum solid solution amount>

[0111] The following is a method for determining the amount of aluminum solid solution in the positive electrode active material. It should be noted that the method is as follows: using aluminum as an amphoteric element, the aluminum-containing compound attached to the surface of the positive electrode active material is dissolved by sodium hydroxide, thereby calculating the aluminum remaining in the positive electrode active material as solid solution aluminum. The aluminum-containing compound dissolved here is considered to be LiAlO2, Li2AlBO4, Li3Al2BO6, etc.

[0112] For a 25 wt% sodium hydroxide solution, mix it in such a way that the proportion of the positive electrode active material becomes 3 wt%, stir it for 1 hour, and then let it stand for 15 minutes to allow the positive electrode active material to settle. Remove the supernatant solution in such a way that the proportion of the positive electrode active material becomes 33 wt%. Add pure water and mix it in such a way that the proportion of the positive electrode active material becomes 5 wt%. By standing for 15 minutes, the positive electrode active material is allowed to settle, and the supernatant solution is removed in such a way that the proportion of the positive electrode active material becomes 33 wt%. After repeating the operation of adding / mixing pure water and removing the supernatant solution 3 times, the positive electrode active material is separated from the solvent by filtration. The filtered positive electrode active material is dried at 150°C for 2 hours in a dryer. The content of aluminum in the positive electrode active material obtained is quantified using an inductively coupled plasma (ICP) emission spectrophotometer. The analytical value obtained is equivalent to the content of aluminum dissolved in the positive electrode active material. The total content of metals other than lithium and aluminum is set to 100 mol% to calculate the aluminum solid solution. That is, it is calculated as (Ni+Co+Mn+Zr):Al=100: aluminum solid solution amount (mol%). In addition, the aluminum solid solution rate (%) is calculated as the ratio of the aluminum content after cleaning to the aluminum content before cleaning. That is, it is calculated as aluminum solid solution rate=content after cleaning / content before cleaning (%). The results are shown in Table 1.

[0113] <Surface compound evaluation>

[0114] The following is a method for confirming the oxide containing lithium and aluminum and the oxide containing lithium and boron attached to the surface of the positive electrode active material. The method is as follows: when sodium hydroxide is used in the above-mentioned determination of the aluminum solid solution evaluation, pure water is used to dissolve the oxide containing lithium and aluminum, so that the oxide containing lithium and aluminum is not dissolved, but the oxide containing lithium and boron is dissolved. As the oxide containing lithium and boron here, LiBO2, Li3BO3, etc. are considered.

[0115] By heat treating a mixture containing lithium transition metal composite oxide particles, a lithium compound, an aluminum compound, and a boron compound, the added aluminum and boron react with lithium to form an oxide, and a portion of the solid solution is formed. The method for evaluating the amount of the solid solution is the above-mentioned aluminum solid solution amount evaluation. The aluminum dissolved by this evaluation forms an oxide with lithium, or forms an oxide with lithium and boron. Therefore, by dissolving the oxides of lithium and boron with pure water, it is possible to infer which element the aluminum reacts with.

[0116] For pure water, mix in a manner that the ratio of the positive electrode active material becomes 3% by weight, stir for 1 hour and then stand for 15 minutes to allow the positive electrode active material to settle. Remove the supernatant solution in a manner that the ratio of the positive electrode active material becomes 33% by weight. Add pure water and mix in a manner that the ratio of the positive electrode active material becomes 5% by weight. By standing for 15 minutes, the positive electrode active material is precipitated, and the supernatant solution is removed in a manner that the ratio of the positive electrode active material becomes 33% by weight. After repeating the operation of adding / mixing pure water and removing the supernatant solution 3 times, the positive electrode active material is separated from the solvent by filtration. The filtered positive electrode active material is dried for 2 hours in a dryer at 150°C. The content of aluminum and boron in the positive electrode active material obtained is quantified using an inductively coupled plasma (ICP) emission spectrophotometer. In addition to the obtained analytical value, the measured solid solution amount of aluminum is used to confirm the Li-Al coating attached in the form of lithium and aluminum oxides and the Li-B coating attached in the form of lithium and boron oxides. When estimated together with the result of the solid solution amount of Example 1 in Table 1, it is believed that the added boron is completely dissolved by washing with pure water, and aluminum is almost not dissolved. According to this result, it is believed that most of the dissolved boron forms oxides of lithium and boron (such as LiBO2, Li3BO3, etc.). In addition, it is believed that most of the aluminum oxide attached to the surface forms oxides containing lithium and aluminum (such as LiAlO2, etc.).

[0117] <Production of evaluation batteries>

[0118] Using the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 to 3, respectively, nonaqueous electrolyte secondary batteries for evaluation were prepared in the following manner.

[0119] [Production of positive electrode]

[0120] 85 parts by mass of positive electrode active material, 10 parts by mass of acetylene black, and 5 parts by mass of polyvinylidene fluoride were dispersed in N-methylpyrrolidone to obtain positive electrode slurry. The obtained positive electrode slurry was applied to a current collector formed of aluminum foil, and after drying, it was compression-molded by a roller press and cut into a given size to obtain a positive electrode.

[0121] [Production of negative electrode]

[0122] 97.5 parts by mass of artificial graphite, 1.5 parts by mass of carboxymethyl cellulose, and 1.0 parts by mass of styrene butadiene rubber were dispersed in water to obtain a negative electrode slurry. The obtained negative electrode slurry was applied to a current collector formed of copper foil, compressed and formed by a roller press after drying, and cut into a given size to obtain a negative electrode.

[0123] [Preparation of non-aqueous electrolyte]

[0124] Ethyl carbonate and methyl ethyl carbonate were mixed at a volume ratio of 3:7 to obtain a mixed solvent. Lithium hexafluorophosphate was dissolved in the obtained mixed solvent to a concentration of 1.0 mol % to obtain a non-aqueous electrolyte.

[0125] [Assembly of non-aqueous electrolyte secondary battery]

[0126] After installing lead electrodes on the collectors of the positive electrode and the negative electrode, they were vacuum dried at 120°C. Next, a separator formed of porous polyethylene was arranged between the positive electrode and the negative electrode, and they were stored in a bag-shaped laminated package. After storage, vacuum drying was performed at 60°C to remove the moisture adsorbed on each component. After vacuum drying, the non-aqueous electrolyte was injected into the laminated package and sealed to obtain a laminated non-aqueous electrolyte secondary battery as an evaluation battery. Using the obtained evaluation battery, the following battery characteristics were evaluated.

[0127] <Evaluation of charge and discharge capacity>

[0128] The charging capacity was measured by constant current and constant voltage charging with a charging voltage of 4.25V and a charging current of 0.2C (1C is the current value at which the discharge ends 1 hour after the full charge state). Next, the discharge capacity was measured by constant current discharge with a discharge voltage of 2.75V and a discharge current of 0.2C. When the charge and discharge capacity of Comparative Example 3 was set as the reference (100%), the specific charge capacity was calculated as Qc (%), and the specific discharge capacity was calculated as Qd (%). The results are shown in Table 1.

[0129] <Evaluation of charge-discharge cycle characteristics>

[0130] A weak current is passed through the obtained evaluation battery for aging, and the electrolyte is fully integrated in the positive and negative electrodes. The evaluation battery is placed in a constant temperature bath at 45°C, and charging at a charging potential of 4.4V and a charging current of 2.0C (1C is defined as the current that completes discharge in 1 hour) and discharging at a discharge potential of 2.75V and a discharge current of 2.0C are regarded as one cycle, and charging and discharging are repeated. The value (%) obtained by dividing the discharge capacity of the 200th cycle by the discharge capacity of the 1st cycle is taken as the discharge capacity retention rate (QsR (%)) of the 200th cycle. The results are shown in Table 1. A high discharge capacity retention rate means good cycle characteristics.

[0131] [Table 1]

[0132]

[0133] According to Examples 1 and 2, both the oxide and hydroxide of the added aluminum compound reduce the capacity reduction by adding aluminum compounds with the same degree of particle size distribution, and the cycle characteristics under high voltage are improved. It is believed that this is because by adjusting the particle size distribution of the added aluminum compound, the two forms of aluminum dissolved in the surface of the primary particles and the oxide containing lithium and aluminum coating the surface of the secondary particles are formed, and the degradation of the positive electrode active material is effectively suppressed with a small addition amount. As in Comparative Examples 1 and 2, even if the same amount of aluminum oxide is added, the cycle characteristics are deteriorated when the volume average particle size is small (Comparative Example 1) and when the total volume ratio of particles above 0.4 μm and below 3.0 μm in the volume-based particle size distribution is small (Comparative Example 2).

[0134] <Evaluation of aluminum distribution using EDX>

[0135] As a method for evaluating the distribution of aluminum in the surface layer of the primary particles, elemental analysis using energy dispersive X-ray analysis (EDX) was performed. Specifically, the measurement was performed using a field emission scanning electron microscope (FE-SEM) (Hitachi High Technologies Co., Ltd., SU8230). As the measurement conditions, the acceleration voltage was 5 kV, EC = 25 μA, and the analysis time was 30 s. The measurement position was the cross-sectional view of the secondary particles in Example 1. Figure 3 At the positions shown in , the black balls representing the surface layer of the primary particles and the white balls representing the inner part of the primary particles were measured. Figure 4 The results of the measurement of the aluminum solid solution in the surface part of the primary particle are shown in FIG. The measurement result of the surface part is the average value of the values ​​measured at 15 locations on one particle for three secondary particles. It should be noted that for the internal part of the primary particle, 5 locations on one particle were measured. In addition, the aluminum solid solution is expressed in mole % when the total amount of nickel, cobalt and manganese is set to 100 mole %.

[0136] like Figure 4 As shown in FIG. 1 , aluminum was detected in the surface layer of the primary particles. On the other hand, aluminum was not detected in the internal part of the primary particles. The same results were obtained for Example 2, Comparative Examples 1 and 2. This indicates that aluminum was not diffused inside the primary particles but only existed in the surface layer of the primary particles. Figure 4 As shown in Comparative Example 1 and Example 1, the smaller the particle size of the aluminum compound, the greater the amount of aluminum present in the surface layer of the primary particles.

[0137] <Measurement of particle size of oxide containing lithium and aluminum after heat treatment>

[0138] The particle size evaluation of the oxide containing lithium and aluminum attached to the surface of the particles was carried out by combining energy dispersive X-ray analysis (EDX) with field emission scanning electron microscopy (FE-SEM). Using images randomly taken by FE-SEM, it was confirmed by EDX that it was an oxide containing lithium and aluminum. For particles containing lithium and aluminum oxides that can be confirmed, the area of ​​the primary particle is calculated by observing the contour confirmed by FE-SEM, and the particle size is measured in the form of an equivalent circle diameter of the area. The particle sizes of more than 100 particles of the measured oxide containing lithium and aluminum were calculated and evaluated. The results are shown in Figure 5 As described above, in the volume-based particle size distribution of the oxide containing lithium and aluminum attached to the surface of the positive electrode active material obtained in Example 1, the total volume ratio of particles with a particle size of 0.4 μm or more and 3.0 μm or less was 99%. On the other hand, in the volume-based particle size distribution of the oxide containing lithium and aluminum attached to the surface of the positive electrode active material obtained in Comparative Example 2, the total volume ratio of particles with a particle size of 0.4 μm or more and 3.0 μm or less was 49%.

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, which has a layered structure and comprises lithium transition metal composite oxide particles containing nickel, and an oxide containing lithium and aluminum and an oxide containing lithium and boron attached to the surface of the lithium transition metal composite oxide particles, The lithium transition metal composite oxide particles include secondary particles formed by aggregation of primary particles having aluminum solid-dissolved on the surface. In the composition of the positive electrode active material for a non-aqueous electrolyte secondary battery, the difference between the ratio of the number of moles of aluminum dissolved in the surface layer of the primary particle to the total number of moles of metals other than lithium and aluminum and the ratio of the number of moles of aluminum present in the region other than the surface layer of the primary particle to the total number of moles of metals other than lithium and aluminum is 0.25 mol% or more and 0.5 mol% or less, wherein the surface layer refers to a depth region from the surface of the primary particle to 100 nm, The oxide containing lithium and boron includes LiBO 2 and / or Li 3 BO 3 , A content ratio of the oxide containing lithium and aluminum to the oxide containing lithium and boron, ie, Al / B, is 0.05 or more and 1 or less in terms of aluminum and boron.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, in, The content of the oxide containing lithium and aluminum relative to the lithium transition metal composite oxide particles is 0.1 mol% or more and 0.8 mol% or less, calculated as the total number of moles of aluminum relative to the total number of moles of metals other than lithium in the lithium transition metal composite oxide particles. The content of the oxide containing lithium and boron relative to the lithium transition metal composite oxide particles is 0.3 mol % or more and 2.0 mol % or less, calculated as the total number of moles of boron relative to metals other than lithium in the lithium transition metal composite oxide particles.

3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, in, In the composition of the lithium transition metal composite oxide particles, a ratio of the number of moles of nickel to the total number of moles of metals other than lithium is 0.33 or more and 0.95 or less.

4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, in, The lithium transition metal composite oxide particles contain cobalt in the composition, and in the composition, the ratio of the number of moles of cobalt to the total number of moles of metals other than lithium is 0.02 to 0.

33.

5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, in, The lithium transition metal composite oxide particles contain manganese in the composition, and in the composition, the ratio of the number of moles of manganese to the total number of moles of metals other than lithium is 0.01 to 0.

33.

6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, in, The lithium transition metal composite oxide has a composition shown in the following formula: Li a Ni b Co c Mr d Al e M 1 f O 2 Where, 1.0≤a≤1.5, 0.33≤b≤0.95, 0.02≤c≤0.33, 0.01≤d≤0.33, 0.0022 <e≤0.05,0≤f≤0.02,b+c+d=1,M 1 It is at least one selected from Zr, Ti, Mg, Ta, Nb and Mo.

7. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, in, In the volume-based particle size distribution of the oxide containing lithium and aluminum, the total volume ratio of particles having a particle size of 0.4 μm or more and 3.0 μm or less is greater than 50%.

8. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, in, The ratio of the amount of aluminum solid solution in the surface layer of the primary particles to the total content of aluminum is 60% or more and 80% or less, The ratio of the amount of aluminum contained in the oxide containing lithium and aluminum adhering to the surface of the secondary particle to the total content of aluminum is 20% or more and 40% or less.

9. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, in, The difference between the ratio of the molar number of aluminum dissolved in the surface layer of the primary particle to the total molar number of metals other than lithium and aluminum and the ratio of the molar number of aluminum present in the area other than the surface layer of the primary particle to the total molar number of metals other than lithium and aluminum is greater than 0.35 mol% and less than 0.45 mol%.

10. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 9, wherein the method include: preparing a mixture having a layered structure and comprising lithium transition metal composite oxide particles containing nickel, a lithium compound, an aluminum compound, and a boron compound; as well as The prepared mixture is heat treated. The lithium transition metal composite oxide particles include secondary particles formed by agglomeration of primary particles. In the volume-based particle size distribution of the aluminum compound, the total volume ratio of particles having a particle size of 0.4 μm or more and 3.0 μm or less is greater than 54%.

11. The manufacturing method according to claim 10, in, The temperature of the heat treatment is 500° C. or higher and 800° C. or lower.

12. The manufacturing method according to claim 10 or 11, in, In the composition of the lithium transition metal composite oxide particles, a ratio of the number of moles of nickel to the total number of moles of metals other than lithium is 0.33 or more and 0.95 or less.

13. The manufacturing method according to claim 10 or 11, in, The lithium transition metal composite oxide particles contain cobalt in the composition, and in the composition, the ratio of the number of moles of cobalt to the total number of moles of metals other than lithium is 0.02 to 0.

33.

14. The manufacturing method according to claim 10 or 11, in, The lithium transition metal composite oxide particles contain manganese in the composition, and in the composition, the ratio of the number of moles of manganese to the total number of moles of metals other than lithium is 0.01 to 0.

33.

15. The manufacturing method according to claim 10 or 11, in, In the volume-based particle size distribution of the oxide containing lithium and aluminum adhering to the surface of the heat-treated lithium transition metal composite oxide particles, the total volume ratio of particles having a particle size of 0.4 μm or more and 3.0 μm or less is greater than 50%.